DAMPAK PANDEMI COVID-19 TERHADAP UMKM DI INDONESIA - Faizi Faizi; Nabila Puspita Wulandana; Audrey Alya; Azzaleya Agashi Lombu (JURNAL LENTERA BISNIS, 2022)
This study aims to determine the impact of the Covid-19 pandemic on the MSME sector. The research uses qualitative methods, namely using a literature review or literature study by looking for sources relevant to the cases discussed, such as research journals, scientific articles, and other sources whose credibility can be recognized. The data collection method is done by data reduction, namely selecting, simplifying, and making conclusions on the data. The instability of the country's economy since the Covid-19 pandemic occurred due to government policies regarding restrictions during the Covid-19 pandemic. As a result of Covid-19, many workers were laid off so that he started his work again by creating a small business, which is commonly called MSME. The sector that has been hardest hit since Covid-19 is MSMEs. In the results of the study, it was found that the results of production and income obtained by MSME entrepreneurs were not comparable to before the existence of Covid-19. In fact, these MSMEs can make a big contribution to the country's economy. In addition, MSMEs also have a big role in reducing unemployment because MSMEs can create jobs for the community. MSMEs are also required to provide new innovations to their products in order to compete with other competitors. The efforts made by MSME activists cannot be separated from government assistance. The government is also required to help small business actors, especially MSMEs, by providing subsidies and stimulus.Keywords: Results, MSMEs, Covid-19, National Economics